X-Ray diffraction analysis of MBE-grown InxGa1-xAs/GaAs superlattices on GaAs (100) substrates - Fernando, Joel G. (National Institute of Physics, College of Science, University of the Philippines Diliman, 2009)
Strained InxGa1-xAs/GaAs superlattices grown on GaAs(100) substrates via Molecular Beam Epitaxy (MBE) are studied. The samples are characterized using non-destructive X-ray diffraction (XRD) measurements and photoluminescence (PL) spectroscopy. The Indium mole fractions and the period thicknesses of the samples are determined using XRD analysis along with standard elasticity theory. Discrepancies in the values of the period thickness and In mole fraction are observed in one sample and are attributed to the generation of misfit dislocations and strain relaxation. XRD short-angle scans, carried out in four azimuthal angles to assess the quality of the superlattices, show that the quality of the samples grown with high In content is inferior compared to samples with low In mole fraction.